2012
DOI: 10.1017/s0021932012000016
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Consanguineous Marriage in Oman: Prevalence, Trends and Determinants

Abstract: The practice of consanguineous marriage has been the culturally preferred form of marriage in most Arab and the Middle Eastern countries, including Oman, but due to a paucity of population-based data in the past there is a dearth of information about its form and dynamics in Oman. Recent national-level surveys allow this gap to be filled. This paper examines the prevalence, trends and determinants of consanguineous marriages in Oman using data from the 2000 Oman National Health Survey. The results indicate a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 47 publications
7
62
3
Order By: Relevance
“…Assuming that the two siblings have the same mutation, it can be seen that phenotypic variations could exist within the same genotypic mutation. Genomic testing of the index case, testing for the carrier state in the asymptomatic siblings as well as in the parents to detect homozygosityor compound heterozygosity is highly recommended especially in a community with a high rate of consanguineous marriage [12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the two siblings have the same mutation, it can be seen that phenotypic variations could exist within the same genotypic mutation. Genomic testing of the index case, testing for the carrier state in the asymptomatic siblings as well as in the parents to detect homozygosityor compound heterozygosity is highly recommended especially in a community with a high rate of consanguineous marriage [12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socially, the marriage simplifies pre-marital negotiations, strengthens family ties, promotes family stability, and offers greater compatibility. Economically, the marriage reduces dowry and preserves property within families (Islam, 2012). In the researcher's study, majority (8 out of 10) of the interviewees are married to their cousins through family arrangements.…”
Section: Challengesmentioning
confidence: 98%
“…b) Second, which is related to the first, many of them are married to their cousins. Consanguineous marriages, especially amongst the first cousins are typical in this society even among the educated and professionals (Peterson, 2011;Islam, 2012). It is preferred and respected due to its social and economic advantages.…”
Section: Challengesmentioning
confidence: 99%
“…In Oman, the prevalence of consanguineous marriage was found to be very high (55%); first-cousin unions were the most common type, constituting 24.1% of all marriages (Rajab & Patton, 2000). Furthermore, another study in the same country also found a high prevalence of consanguinity (52%), and first-cousin marriages were found to be 39% of all marriages (Islam, 2012). In a recent study in Tunisia, first-cousin marriages were found to be the most common type of consanguineous marriages and accounted for 31.8% of the overall sample studied, but they constituted 55.5% of all consanguineous unions (Halim et al, 2013).…”
Section: Introductionmentioning
confidence: 94%